2002
DOI: 10.1300/j122v23n01_02
|View full text |Cite
|
Sign up to set email alerts
|

Why Does One Choose Sci-Tech Librarianship?

Abstract: A questionnaire survey was conducted to determine why librarians found themselves working in sci-tech library positions. Openended questions were included in the survey to solicit personal opinions and anecdotes regarding the choice of sci-tech librarianship. Three hundred eleven responses were received.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 3 publications
0
16
0
Order By: Relevance
“…In Winston's [16] review of the literature on the educational backgrounds of librarians in science and engineering libraries, surveys in the 1980s and 1990s indicate that between 18% and 67% of librarians have some kind of university science degree. A study by Hackenberg and Chu [17] on the academic backgrounds of science librarians showed that librarians:…”
Section: Discussionmentioning
confidence: 99%
“…In Winston's [16] review of the literature on the educational backgrounds of librarians in science and engineering libraries, surveys in the 1980s and 1990s indicate that between 18% and 67% of librarians have some kind of university science degree. A study by Hackenberg and Chu [17] on the academic backgrounds of science librarians showed that librarians:…”
Section: Discussionmentioning
confidence: 99%
“…These results echo research in the librarian recruitment literature that debates the necessary educational backgrounds for successful health sciences and science and technology librarians. The consensus in the literature is that having a strong interest in science and a motivation to develop oneself professionally are better determinants of success than educational background and that the best predictor of success is the librarians' personal efforts prioritizing their own professional development [13][14][15][16][17]. Indeed, the e-science web portal has the potential to play a major role in this professional development for those respondents who did not have a medical or other related science background.…”
Section: Discussionmentioning
confidence: 99%
“…Journal article (41) Thesis Emanuel (2012) Type of Publication Conference Proceedings (3) Hallam and Partridge (2005), Bavakutty et al (2008), Newbutt and Sen (2008) Farley-Larmour (2000), Hackenberg (2000), Adomi and Ogbomo (2001), Deeming and Chelin (2001), Fikar and Corral (2001), Marcella and Baxter (2001), Winston (2001), Hallmark and Lembo (2003), Hackenberg and Chu (2004), Figyelo (2005), Ard et al (2006), Luzius (2006), Berry (2007), Davis (2007), Eells (2007), Kim et al (2007), Stanley (2007), Hines and Baker (2008), Issa and Nwalo (2008), Lian and Xiong (2008), Shannon (2008), Unagha (2) IFLA conference proceedings (3) Conference Proceedings …”
Section: Choice Of Library and Information Sciencementioning
confidence: 99%